Lean manufacturing in the north furniture polo of Santa Catarina from the perspective of strategic planning - Peter Cristian Lother; Romano Timofeiczyk Junior; Vítor Afonso Hoeflich; Saulo Henrique Weber (Semina: Ciências Exatas e Tecnológicas, 2022)
This article aims to investigate the process of implementation of Lean Manufacturing (LM) in companies in the North Furniture Center of Santa Catarina, seeking to identify its adherence to the concepts of strategic planning to ensure its success, within a log-term perspective. This article is based on a qualitative search with this furniture center to identify elements, through data analysis that allowed understanding the dynamics that were applied in this process of LM implementation and its interface with the strategic operations planning. Thus, as a result of this research, the study presented the main characteristics and behaviors related to the concepts of strategic planning aligned with this LM implementation process, which were found: staff training, communication, support for problem solving, monitoring of indicators, review and regular improvements. The study provided important guidance on the best practices for a consistent process for implementing the LM in order to obtain more robust and sustainable results for companies through the commitment of employees